Exploring how NPO leaders maintained effective organisational performance amid the Covid-19 pandemic - Mncube, Thembekile (Department of Social Development, 2024)
For an organisation to function effectively and accomplish its goals, it must have effective leaders, who can lead the organisation towards the fulfilment of its objectives. The onset of the Covid-19 pandemic affected the organisational performance of companies and NPOs across the globe, and it was the responsibility of organisation leaders to develop strategic action plans for how to maintain the achievement of their goals during these turbulent times. In this study, a qualitative research design was utilised to explore how NPO leaders maintained effective organisational performance amid the Covid-19 pandemic. Leaders from a sample of 16 non-profit organisations, based in the Western Cape, were purposively selected to voluntarily participate in the study by means of a virtual interview. According to the findings of this study, the leaders were responsible and effective which contributed to the maintenance of positive organisational performance. The Covid-19 crisis led organisations to suffer from financial issues and made it difficult for organisations to function virtually. Conversely, working virtually created hybrid working conditions that participants appreciated. Participants were resilient and agile, they empowered and motivated employees and clearly articulated their plans and worked with their colleagues, stakeholders, and partners, which contributed to participants meeting their goals and maintaining operations. It is recommended that leaders implement solutions, such as ensuring a wide pool of funders to mitigate the issue of NPOs struggling financially amid any crisis. Furthermore, the provincial government, through the Department of Social Development, should assist NPOs to develop financial sustainability plans that may be implemented to assist them in achieving financial sustainability.